Snakebite Envenoming Diagnosis and Diagnostics - Knudsen, Cecilie; Jürgensen, Jonas A.; Føns, Sofie; Haack, Aleksander M.; Friis, Rasmus U. W.; Dam, Søren H.; Bush, Sean P.; White, Julian; Laustsen, Andreas H. (Frontiers in Immunology, 2021)
Snakebite envenoming is predominantly an occupational disease of the rural tropics, causing death or permanent disability to hundreds of thousands of victims annually. The diagnosis of snakebite envenoming is commonly based on a combination of patient history and a syndromic approach. However, the availability of auxiliary diagnostic tests at the disposal of the clinicians vary from country to country, and the level of experience within snakebite diagnosis and intervention may be quite different for clinicians from different hospitals. As such, achieving timely diagnosis, and thus treatment, is a challenge faced by treating personnel around the globe. For years, much effort has gone into developing novel diagnostics to support diagnosis of snakebite victims, especially in rural areas of the tropics. Gaining access to affordable and rapid diagnostics could potentially facilitate more favorable patient outcomes due to early and appropriate treatment. This review aims to highlight regional differences in epidemiology and clinical snakebite management on a global scale, including an overview of the past and ongoing research efforts within snakebite diagnostics. Finally, the review is rounded off with a discussion on design considerations and potential benefits of novel snakebite diagnostics.